Fragmentos capilares provocando paroniquia e onicolise em barbeiros/cabeleireiros: Uma dermatose ocupacional - Haddad Júnior, Vidal [UNESP]; Neto, Chafi Facouri [UNESP]; Dillon, Neuza Lima [UNESP] (My University, 1999)
By means of observation of hair fragments provoking paronychia and onycholysis in a barber, the authors performed a epidemiological investigation in others barbers/hair-dressers of Botucatu (SP), that showed a high frequency of die dermatosis.
Hair fragments provoking paronychia and onycholysis in barbers/hair- dressers: An occupational dermatosis
Keywords: Onycholysis; Paronychia; Tricogranulomas; adult; aged; case report; hair; hairdresser; human; image analysis; male; occupational eczema; occupational hazard; onycholysis; paronychia; skin manifestation